Natural Properties in Ethics with an Emphasis on Shafer-Landau’s Theory - Hassan Heshmati; Muhammad Legenhausen; Hassan Miandari (Pizhūhish/hā-yi Falsafī- Kalāmī, 2018)
Various criteria for the natural/non-natural distinction have been suggested in metaethics. Shafer-Landau first claimed that natural properties are properties that are used in scientific disciplines. But firstly, this definition is not comprehensive, and secondly it is ambiguous; according to the second criterion, two lists must be prepared; the first list includes terms that most people consider to be natural. The terms that are not included in the first list, are transferred to the list of non-natural terms. I argue, however, that this criterion also does not help in distinguishing natural properties from non-natural ones. If we wish to maintain Shafer-Landau's view, we can find a criterion for natural properties using normative ethics. For example, by accepting Kant’s principle of humanity as a non-natural reality, those descriptive properties that follow from this principle can be the foundational properties for moral properties. But by presenting a serious criticism on Shafer-Landau's metaethics and accepting views that are invulnerable to this critique, a criterion for the distinction of natural/non-natural in meta-ethics can be found. One of these views is Fitzpatrick’s view, according to which many of the aspects of the world that are empirically investigable are also inherently value-laden. Therefore, the world of human experience is a dual-aspect world. One of these aspects is natural and the other is non-natural.